Fresno County Bar Association Witkin Luncheon at Hilton Hotel with Bernard Witkin - Watkins, Howard::::::::: (1986)
Judge Harold Thompson, Jean Thompson, Bernard Witkin, Roger Tatarian, Judge James V. Paige and Alba Witkin